2012
DOI: 10.1270/jsbbs.61.618
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of foxglove aphid (Aulacorthum solani) resistance gene Raso1 in soybean and its effect on tolerance to Soybean dwarf virus transmitted by foxglove aphid

Abstract: Soybean dwarf virus (SbDV) causes serious dwarfing, yellowing and sterility in soybean (Glycine max). The soybean cv. Adams is tolerant to SbDV infection in the field and exhibits antibiosis to foxglove aphid (Aulacorthum solani), which transmits SbDV. This antibiosis (termed “aphid resistance”) is required for tolerance to SbDV in the field in segregated progenies of Adams. A major quantitative trait locus, Raso1, is reported for foxglove aphid resistance. Our objectives were to fine map Raso1 and to reveal w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The average number of aphids per plant was used as a basis for identifying aphid resistance in bean (Han et al 1991). There is evidence for genetic control of aphid resistance in many crops, including tomato (Solanum lycopersicum) (Rossi et al 1998), wheat (Triticum aestivum) (Liu et al 2005), barley (Hordeum vulgare) (Mittal et al 2008), melon (C. melo) (Sarria et al 2008;Brotman et al 2002), barrel clover (Medicago truncatula) (Klingler et al 2005), maize (Zea mays) (So et al 2010) and soybean (Glycine max) (Kim et al 2010a, b;Ohnishi et al 2012). However, little is known about the inheritance of aphid resistance in cucumber.…”
Section: Introductionmentioning
confidence: 99%
“…The average number of aphids per plant was used as a basis for identifying aphid resistance in bean (Han et al 1991). There is evidence for genetic control of aphid resistance in many crops, including tomato (Solanum lycopersicum) (Rossi et al 1998), wheat (Triticum aestivum) (Liu et al 2005), barley (Hordeum vulgare) (Mittal et al 2008), melon (C. melo) (Sarria et al 2008;Brotman et al 2002), barrel clover (Medicago truncatula) (Klingler et al 2005), maize (Zea mays) (So et al 2010) and soybean (Glycine max) (Kim et al 2010a, b;Ohnishi et al 2012). However, little is known about the inheritance of aphid resistance in cucumber.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some genes or QTLs for resistance to abiotic or biotic stresses in soybean have been mapped near the region of RpsGZ on chromosome 3. For instance, the QTL Raso1 for major foxglove aphid resistance was mapped to a 63-kb interval containing an NBS-LRR-type R-like gene and two other genes in the Williams 82 sequence assembly [63]. A minor foxglove aphid resistance QTL in PI 366121 [64], two soybean sudden death syndrome resistance QTLs, di1 [65,66] (also known as qRfs6 [67]) and SDS14-1 [68], and the major QTLs or dominant loci underlying salt tolerance in the soybean cultivars Tiefeng8 and Jidou12 [69,70] might be clustered in the region as Rps resistance genes.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, developing foxglove aphid resistance plant is an economically efficient strategy to avoid yield losses by foxglove aphid. Currently, only one resistance gene, Raso1 from Adams, has been identified in soybean, which is responsible for the foxglove aphid resistance and mapped on chromosome 3 (Ohnishi et al 2012). Also, metabolite research showed that foxglove aphid resistance from Tohoku 149 was related to sulfur metabolism and methylation due to two methylated metabolites, S-methylmethionine and trigonelline (Ohnishi et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports suggested that foxglove aphid prefers fresh tissues; however, recent research indicated that mature leaves are preferred over growing tips or young leaves (Jandricic et al 2014). Raso1, a foxglove aphid resistance QTL, was isolated from the cultivar 'Adams' (Weiss 1953) and mapped on chromosome 3 (Ohnishi et al 2012). Sato et al demonstrated that Tohoku 149 showed foxglove aphid resistance (Sato et al 2013(Sato et al , 2014.…”
Section: Introductionmentioning
confidence: 99%